Desenvolvimento e políticas públicas: uma avaliação do PRONAF nos assentamentos de reforma agrária do Rio Grande do Norte - Silva, Dalvanir Avelino da (2012)
The research DEVELOPMENT AND PUBLIC POLICY: AN EVALUATION OF PRONAF IN THE SETTLEMENTS AGRARIAN REFORM OF RIO GRANDE DO NORTE aimed to evaluate the effectiveness of the National Program for Strengthening Family enhancerelement od development in rural settlements od Rio Grande do Norte. The methodological approach consisted of the completion of desk research and literature on development issues, policies, and rural credit and field research through semi- structured interviews with managers and technicians who work with the program and conducting focus with farmers settles who accessed the PRONAF the period from 2000 to 2006. The survey results confirm the central hypothesis of this work, that acces to PRONAF A is not causing efetivations relevant in the lives of farm workers settlers in Rio Grande do Norte. In the setllements where efetivations these occur, they are short of what the program intends to carry out and rely on a set of conditionalities that are beyond the operational frameworks of the same. Such questions point to the need to revise the program in order to estabilish adjustments that in practice the approach of the proposed objectives. For this purpose it is necessary to invest in factor that contribute to the program has a positive effect not only to increase income, but to contribute to the autonomy of the resettled farmers, expanding its capabilities and increased the power of choise with respect to life who wish to take